INTERAKSI SOSIAL DALAM MEMBANGUN CITRA SUPORTER THE JAKMANIA KARAWANG - Hilal Aulia Pasya; Siti Nursanti; Luluatu Nayiroh (Metacommunication: Journal of Communication Studies, 2022)
This research is used to explore the pattern of social interaction in building the image of the group of supporters of The Jakmania Karawang. Over time, The Jakmania Karawang has obstacles and a negative image as a form of unity by The Jakmania Karawang. The research is a case study approach and method. Sources of data using data collection techniques are descriptive observation, structured interviews, documentation in the form of pictures. The subject of this research is the regional coordinator and member of the field coordinator of The Jakmania Karawang. The data analysis technique uses the Miles and Huberman model whose contents are data collection, data reduction, data presentation, and conclusions. This study uses the Interaction Analysis Theory proposed by Aubrey Fisher, Leonard Hawes. This theory discusses the interaction process in which a person gives suggestions, feedback, and expects responses from group members. The results of the research found are patterns of social interaction that occur in the form of social contact in the form of social media, discussions, and casual chat. Communication that is formed is verbal communication, two-way and results in direct communication, and group communication. The forms of associative social interaction in the form of kinship, cooperation, embracing, mutual cooperation, and solidarity form conciliation and tolerance, forms of dissociative social interaction in the form of individual and intergroup conflicts and conflicts produce culture. Barriers to patterns of social interaction because they have a distinctive language are different, the driving factor that hinders due to conflict in fanaticism.Kata Kunci: Pola interaksi sosial, kelompok, citra.